2018
DOI: 10.1371/journal.pone.0206636
|View full text |Cite
|
Sign up to set email alerts
|

Exploring natural genetic variation in tomato sucrose synthases on the basis of increased kinetic properties

Abstract: Sucrose synthase (SuSy) is one key enzyme directly hydrolyzing sucrose to supply substrates for plant metabolism, and is considered to be a biomarker for plant sink strength. Improvement in plant sink strength could lead to enhanced plant growth and yield. Cultivated tomatoes are known to have a narrow genetic diversity, which hampers further breeding for novel and improved traits in new cultivars. In this study, we observed limited genetic variation in SuSy1, SuSy3 and SuSy4 in 53 accessions of cultivated tom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…The data used for comparison were publicly available tomato genomes from two studies (Dinh et al 2018;Lin et al 2014;Tomato Genome Sequencing et al 2014), for a total of 444 re-sequenced genomes of tomato cultivars and closely related species.…”
Section: Resultsmentioning
confidence: 99%
“…The data used for comparison were publicly available tomato genomes from two studies (Dinh et al 2018;Lin et al 2014;Tomato Genome Sequencing et al 2014), for a total of 444 re-sequenced genomes of tomato cultivars and closely related species.…”
Section: Resultsmentioning
confidence: 99%
“…Sucrose synthases are a group of key enzymes responsible for catalyzing reversible reactions of sucrose decomposition and synthesis [ 38 ]. It has been reported that in the sucrose metabolism pathway, gene expression and enzyme activity associated with sucrose catabolism (SUS, invertase, etc.)…”
Section: Discussionmentioning
confidence: 99%
“…This finding implies that the distinct sucrose metabolism in both leaves and fruits of wild accession LA385 could be one of the keys to support its higher photosynthetic capacity compared to that in Moneymaker. We have shown in a recent study that the heterologously expressed protein sucrose synthase 3 (SUSY3) of LA385 could hydrolyze sucrose more efficiently compared to the counterpart of Moneymaker (Dinh et al, 2018). Additionally, SUSY has been shown to interact with multiprotein complex involved in cellulose/callose biosynthesis in main crops such as cotton, tobacco, and wood (Nakai et al, 1999, Persia et al, 2008, Coleman et al, 2009, Fujii et al, 2010).…”
Section: Discussionmentioning
confidence: 99%